Motor cortex layer 4: less is more. Issue 5 (May 2015) - Barbas, Helen; García-Cabezas, Miguel Á.
<x xml:space="preserve">Abstract</x> The stratified motor cortex is variously thought to either lack or contain layer 4. Yamawaki et al. described a functional layer 4 in mouse motor cortex with properties and connections similar to layer 4 in sensory areas. Their results bolster a theoretical framework suggesting all primary cortical areas are equivalent.